Food systems among Native American peoples in Oakland, California: an examination of connection and health - Vernon, Rachel Valerie, author; Cespedes, Karina, advisor; Souza, Caridad, committee member; Pickering, Kathleen, committee member (Colorado State University. Libraries, 2014)
This thesis is a critical engagement with Indigenous communities and the reclamation of food sovereignty as a movement that heals Indigenous populations. The Indigenous food sovereignty movement stands in opposition to a history of colonialism and disenfranchisement that sought to deny Indigenous people of their autonomy by creating dependency on Western institutions. Reclamation of a food system stands to signify the healing of community through the honoring of relationships and interdependence. Contemporary scholarship and policy efforts addressing health disparities have focused the debate on Indigenous food and health around personal accountability, and personal choice in eating and exercising. Although these behaviors improve health for communities, and individuals, they do not account for systemic disparities forged out of a history of colonialism and current institutional racism. Moreover, this focus is deeply engrained in Western models of health, rather than promoting the power of communities to forge their own culturally appropriate solutions. These mainstream attempts by Western institutions are singular in nature, denying the complex interaction at multiple points of colonialism and racism. This thesis focuses on Indigenous food sovereignty, and in particular attempts at urban community production, to address the emancipatory act of reclaiming traditional knowledge and the right to feed oneself and one's community. Food sovereignty is an ideological, cultural, and political act that can transform Indigenous communities that are "dying to survive" and transform them into thriving communities. This Indigenous food justice movement honors native peoples as visionary survivors of catastrophe. Using Indigenous methodology and photovoice I provide an analysis of one urban community in Oakland California where participants have been engaged in reclaiming their food system since 2010. This project allows us to understand how empowerment (of self and community) as well as relationships are strengthened because of such projects.
Keywords: community owned food systems